Prevalence of C-shaped Canals and Three-rooted Mandibular Molars Using CBCT in a Selected Thai Population - Hiran-us, Sirawut; Benjavongkulchai , Sunpatch; Antanit , Chidnarong; Thanadrob, Pornthip; Thongpet , Pakjira; Onrawijit , Apichai (Iranian Endodontic Journal, 2021)
Introduction: C-shaped canals and three rooted mandibular molars are challenging to treat. These anatomies are commonly found in mandibular molars, especially in the Mongoloid population. However, there is no report on these anatomies using cone-beam computed tomography on all three mandibular molars in Thais. The objectives of this study were to determine the prevalence of C-shaped canals and three-rooted mandibular molars in Thais and investigate whether there is a relationship between these morphology and gender. Methods and Materials: Three pre-calibrated observers independently determined the presence of each anatomy using a specific protocol in 753 molars from cone-beam computed tomographic images. The three observers randomly re-evaluated 20% of the samples to determine inter- and intra-observer agreement using Cohen’s Kappa statistic. The relationship of these root canal anatomy with sex was analysed by the Chi-square test. Results: The prevalence of C-shaped canals and three-rooted molars was 0.39% and 12.1%, 42.4% and 3.9%, and 16.6% and 9.1% in first, second, and third mandibular molars respectively. The inter-/intra-observer reliability of the results was extremely high. Conclusion: This cross-sectional study showed the prevalence of C-shaped canals in mandibular second molars was relatively high and should be considered normal root canal anatomy in Thais. The prevalence of three-rooted molars was highest in first molars and frequently found in third molars. Cone-beam computed tomography was a reliable technique to determine root canal anatomy.